A rise in the frequency of lasR mutant Pseudomonas aeruginosa among keratitis isolates between 1993 and 2021 - Shanks, Robert M. Q.; Atta, Sarah; Stella, Nicholas A.; Sundar-Raj, Chollapadi V.; Romanowski, John E.; Grewal, Arman S.; Shanks, Hazel Q.; Mumper, Sonya M.; Dhaliwal, Deepinder K.; Mammen, Alex; Callaghan, Jake D.; Calvario, Rachel C.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Pseudomonas aeruginosa causes vision threatening keratitis. The LasR transcription factor regulates virulence factors in response to the quorum sensing molecule N-3-oxo-dodecanoyl-L-homoserine lactone. P. aeruginosa isolates with lasR mutations are characterized by an iridescent high sheen phenotype caused by a build-up of 2-heptyl-4-quinolone. A previous study demonstrated 22% (n=101) of P. aeruginosa keratitis isolates from India between 2010 and 2016 were sheen positive lasR mutants, and the sheen phenotype correlated with worse clinical outcomes for patients. In this study, a longitudinal collection of P. aeruginosa keratitis isolates from Eastern North America were screened for lasR mutations by the sheen phenotype and sequencing of the lasR gene. Methods Keratitis isolates (n=399) were classified by sheen phenotype. The lasR gene was cloned from a subset of isolates, sequenced, and tested for loss of function or dominant-negative status based on an azocasein protease assay. A retrospective chart review compared outcomes of keratitis patients infected by sheen positive and negative isolates. Results A significant increase in sheen positive isolates was observed between 1993 and 2021. Extracellular protease activity was reduced among the sheen positive isolates and a defined lasR mutant. Cloned lasR alleles from the sheen positive isolates were loss of function or dominant negative and differed in sequence from previously reported ocular lasR mutant alleles. Retrospective analysis of patient information suggested significantly better visual outcomes for patients infected by sheen positive isolates. Discussion These results indicate an increase in lasR mutations among keratitis isolates in the United States and suggest that endemic lasR mutants can cause keratitis.